Critical reflection on critical thinking and TEM tests of English major students’ performance - Ya Luo (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
Critical thinking is now called for modern age of educational management, due to education can prepare children and citizen to face with uncertainty of changing world. Complexity of modern world is adapting with a ton of knowledge and millions of situations that shape our children to face with uncertainty. The article aims to critical reflection on critical thinking and TEM tests of English major students’ performance. Skills-based learning in terms of English for minority group is important for quality of education. Educators could not ignore the phenomenon that students lack of critical thinking through various sources of learning and testing. The point of reflection needs to cultivate students’ abilities in independent thinking, innovation, analysis and critical awareness in order to achieve a better goal in language teaching.